Clinical and Radiographic Correlates for the Treatment of Ulnocarpal Impaction - Mwaturura, Tendai; Daneshvar, Parham; Pike, Jeffrey; Goetz, Thomas Joseph (Journal of Wrist Surgery, 2019)
Background Ulnocarpal impaction (UCI) is a described cause of ulnar side wrist pain.Questions Does absolute ulnar variance (UV) or change in UV with grip affect patient-rated outcome scores (PROS) in patients with symptomatic UCI undergoing surgery? Does UV differ between symptomatic and contralateral wrists? Does arthroscopic grade of triangular fibrocartilaginous complex (TFCC) tears and lunotriquetral (LT) ligament tears influence PROS? Do PROS improve following ulnar shortening osteotomy (USO) or wafer procedures and does improvement depend on the amount of shortening or achievement of negative UV?Patients and Methods We analyzed information on patients undergoing USO or wafer procedures for UCI as recorded in a database of prospectively collected information on individuals with ulnar side wrist pain. This included (1) patient-rated wrist evaluation and QuickDASH scores on enrolment, 3 and 12 months postoperatively; (2) standardized bilateral posteroanterior (PA) wrist radiographs, including PA grip views of the symptomatic wrist; and (3) arthroscopic findings.Results Larger changes in UV between PA neutral and grip views prior to surgery were associated with smaller improvements in PROS, 12 months after surgery. Actual UV value before and after surgery did not affect PROS. There was no difference in UV between symptomatic and contralateral wrists. The presence of TFCC or LT ligament tears did not influence PROS. Mean PROS improved postoperatively.Conclusions Ulnar shortening procedures result in improvement in PROS in patients with UCI. Variation in UV with rotation and grip results in variable outcomes.Level of Evidence This is a Level II, cohort study.
Keywords: ulnocarpal impaction; ulnar variance; pronation and grip; ulnar shortening osteotomy; wafer procedures; patient-rated outcome scores; radiographs; wrist arthroscopy